2018
DOI: 10.1038/s41438-018-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analyses identify albino-associated genes of a novel albino tea germplasm ‘Huabai 1’

Abstract: Albinism in shoots of tea plants is a common phenotypic expression which gives the tea infusion a pleasant umami taste. A novel natural albino mutant tea germplasm containing high amino acids content was found and named as ‘Huabai 1’. ‘Huabai 1’ has white jade tender shoots under low temperature and turns green with increased temperature. In order to understand the molecular mechanism of color change in leaf of ‘Huabai 1’, transcriptome analysis was performed to identify albino-associated differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…The molecular mechanism and chemical composition of tea plant germplasms with unique leaf color have attracted increasing research attention. However, the detection methods of the compounds and the genetic background of the materials limit further research [14,17]. In this study, natural yellow-leaf mutants of the Rougui cultivar were obtained, and a combination of high-throughput and high-sensitivity widely targeted metabolomics and transcriptomics was performed using young shoots from YR and GR to gain insight into the differences in chemical components and gene regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism and chemical composition of tea plant germplasms with unique leaf color have attracted increasing research attention. However, the detection methods of the compounds and the genetic background of the materials limit further research [14,17]. In this study, natural yellow-leaf mutants of the Rougui cultivar were obtained, and a combination of high-throughput and high-sensitivity widely targeted metabolomics and transcriptomics was performed using young shoots from YR and GR to gain insight into the differences in chemical components and gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…"Huangjinya" and "Yu-Jin-Xiang" are typical light-sensitive mutants with yellow shoots under strong light and return to green once the light intensity is reduced [9][10][11]. Previous studies have found that the shoots of albino cultivars contain higher levels of amino acids and lower levels of catechins, carotenoids, chlorophyll, and total content of most endogenous free tea aromatics than green tea cultivars [2,[12][13][14][15]. However, most tea plant materials are not suitable materials for studying the molecular mechanisms of leaf color because of their different genetic backgrounds [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the two enzymes phenylalanine ammonia lyase and cinnamoyl-CoA reductase are mainly involved in lignin biosynthesis. The biosynthesis of lignin is a major branch of phenylpropane biosynthesis, and the biosynthesis of phenylpropane is involved in the resistance of plants to diseases [37][38][39]. In this study, we found ve common DEPs in the two comparison groups of S1-3dpi/S1-0dpi and S2-3dpi/S2-0dpi to be signi cantly down-regulated, including ProDH, 4-hydroxy-7-methoxy-3-oxo-3,4-dihydro-2H-1,4benzoxazin-2-yl glucoside beta-D-glucosidase, Beta-glucosidase 26, AOS, and GSTU1.…”
Section: Discussionmentioning
confidence: 99%
“…She found that CLH, RCCR and SGR were signi cantly high expression in the golden bud, and their chlorophyll synthesis genes were inhibited, resulting in the insu cient chlorophyll content after 40 days of shading. The degradation of chlorophyll in Anji Baicha and Huabai 1 was accelerated and the leaves became white [14,15].…”
Section: Introductionmentioning
confidence: 99%